Kontribusi Life Skill Education dan Self-Efficacy terhadap Kematangan Karier Siswa di SMAN 1 Majalaya - Zanzabil, Realuddin Ainun; Alfaiz, Alfaiz; Rafiola, Ryan Hidayat; Julius, Andre; Valdez, Anabelie Villa (Institut Agama Islam Negeri Kerinci, Indonesia, 2025)
Life Skills Education and self-efficacy is an important thing to mastery by a students. Career maturity is an important that has relation with how much we struggle for achieve something, and also self-efficacy as a psychological aspect for competency and capacity in academic. This study uses Inferential quantitative research methods. Descriptive statistics are methods related to the collection and presentation of data so as to provide useful information. Research on the description of Life Skills Education and self-efficacy in classes X, XI, XII at SMA Negeri 1 Majalaya. Research on the description of career maturity in classes X, XI, XII is included in the medium and low category. The influence of the independent variable (Life Skills Education and self-efficacy) on the dependent variable (career maturity) is 39.1%. The results of statistical testing on research obtained career maturity influenced by Life Skills Education and self-efficacy. 1. The description of Life Skills Education in classes X, XI, and XI in general is in the medium category. 2. The description of self-efficacy in grades X, XI, and XII is generally in the low category. 3. The description of Career Maturity in grades X, XI, and XI is generally in the medium category. 4. Based on the results of regression analysis in this study, it is found that Life Skills Education and self-efficacy has significantly a contribution to a students' career maturity